Agnus Dei: cordero de Dios - Sánchez, Alejandra (France : CAT&Docs, 2010)
"Agnus Dei" is a candid documentary on the thorny subject of pedophilia in the Catholic Church. As an 11-year-old altar boy Jesús, now 26, was abused by a priest. Father Carlos, a priest and paternal figure respected by the community and seen as an unimpeachable authority, intimidated Jesús into long years of silence. Years later, however, Jesús decides not only to tell his story but also to bring criminal charges against his aggressor, and confront him in person. This is the story of his journey, a mandatory hiatus on the road to forgiveness, born of a deep-seated need to come to terms with the past. Jesús is torn between brotherly love and anger toward his sexual predator in this film full of nuances that gives a name and a face to a problem stigmatized by silence.
Verzio Film Festival Submission ; Coproduction: France, Mexico
Verzio Film Festival Submission
Keywords: Documentary films